Peningkatan Imunitas Ibu Nifas Melalui Senyawa Flavonoid Hasil Ekstraksi Lemon (Citrus Limon) Menggunakan Teknologi Ultrasound Assisted Extraction - Septiani, Camilla; Widyawati, Melyana Nurul; Kurnianingsih, Kurnianingsih; Sudiyono, Sudiyono; Susanto, Edy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of the extraction of lemon liquid (citrus limon) using Ultrasound Assisted Extraction (UAE) technology against increasing the immunity of puerperal mothers. The method used is true experiment with randomized pretest and posttest with control group design. The results showed that the average increase in immunity of postpartum mothers in the pretest intervention group was 264.66 and posttest was 328.16 while in the control group the average result of increasing immunity was 208.76 and posttest was 137.05. The conclusion of giving the results of the extraction of lemon liquid (citrus limon) using Ultrasound Assisted Extraction (UAE) technology at a dose of 7grams / 175ml given for 14 days was proven to have an effect on increasing the immunity of postpartum mothers with a p value of <0.05. Keywords : Immunity, Mother Puerperium, Flavonoid Compounds, Lemon Extraction, Ultrasound Assisted Extraction (UAE).